(untitled) (Scientific journal of the Fergana State University, 2019)
In the article the author investigates the matters of insertion of the innovations in new conditions as an important factor of a sustainable development of a society. The attempt to connect modern problems of perfection of system of insertion of innovations in society with reforming processes in the country is made.